Entrepreneurship: Cause or consequence of financial optimism? - Christopher Dawson; David Emmanuel De Meza; Andrew Henley; G. Reza Arabsheibani (Institute for the Study of Labor (IZA), 2012)
Extant evidence that the self-employed overestimate their returns by more than employees do is consistent with two mutually inclusive possibilities. Self-employment may generate optimism or optimists may be drawn to self-employment. This paper finds that employees who will be self-employed in the future overestimate their short-run financial wellbeing by more than those who never become self-employed. When actually self-employed they are even more optimistic. Employees aspiring to start their own business are also of above average optimism. Cross-sectional findings are therefore an amalgam of psychological disposition and environmental factors, as theory requires if optimism is to be a causal influence on entrepreneurship.
Keywords: D84; M13; 330; financial optimism; expectations; self-employment; Selbstständige; Private Finanzplanung; Erwartungstheorie; Persönlichkeitspsychologie; Schätzung; Großbritannien